Association of HFE Gene Polymorphism and Ferritin with the Iron Overload in β-Thalassemia Major Patients. - al sultany, mustafa; Mohammad, Heyam Qaid (Hammurabi Journal of Medical Sciences, 2024)
Background: The human hemochromatosis protein HFE is encoded by the HFE gene and participates in iron regulation. Objectives: to detect the most frequent HFE gene mutations in a control population and genotype thalassemia major. Material and Methods: A total of 100 individuals (50 normal and 50 patients) were examined. Genetic diagnosis of HFE gene polymorphisms was performed by Conventional polymerase chain reaction (PCR) analysis. Results: The heterozygous rs1799945 (CG) genotype was significantly among β-TM patients than in controls (p = 0.041) and the homozygous (GG) genotype was significantly higher among β-TM patients than in controls (p = 0.008). Odds ratio [OR](CG, GG) = 0.28 and 0.28, 95% confidence interval [CI] = [0.08-0.95], [0.11-0.72], respectively). The results show that there is a highly significant allelic frequency difference between case and control groups (P= 0.0003). The heterozygous rs1800562 (GA) genotype was significantly higher among β-TM patients than in controls (p = 0.028) and the homozygous (AA) genotype was significantly among β-TM patients than in controls (p = 0.052). Odds ratio [OR] (GA, AA) = 0.27 and 0.35, 95% confidence interval [CI] = [0.08-0.87], [0.12-1.01] , respectively). The results show that there is highly-significant allelic frequency difference between case and control groups (P= 0.003). Serum levels of ferritin in patients with β-thalassemia major patients were higher than control the mean ± standard deviation patients groups (2008.44 ± 690.39) and (84.59 ± 21.27) in control group, the difference was highly significant (P< 0.001). Conclusion: This study shows that as there is a correlation between HFE mutation and ferritin levels the presence of HFE mutation may be a predictor of susceptibility to iron overload due to high level of ferritin in Beta thalassemia patient.